Lipoprotein(a) level assessment in internal medicine patients: cardiological vs. non-cardiological admissions - Szczupak, Piotr; Pawlos, Agnieszka; Krakowska, Natalia; Broncel, Marlena; Gorzelak-Pabiś, Paulina (Medical Studies/Studia Medyczne, 2026)
Abstract Introduction: Lipoprotein(a) [Lp(a)] is a lipid molecule similar to low-density lipoprotein cholesterol (LDL-C). Elevated Lp(a) has been associated with increased risk of atherosclerosis. Aim of the research: The purpose of the study is to perform a screening analysis of Lp(a) levels in patients admitted to the Department of Internal Diseases, irrespective of whether their hospitalization is related to cardiological or non-cardiological reasons. Material and methods: The study included 104 patients admitted to the Department of Internal Diseases and Clinical Pharmacology between 2 July 2021, and 3 December 2021, excluding those admitted due to SARS-CoV-2 infection. Patients were analysed based on the presence of atherosclerosis, Lp(a) levels, and other laboratory values. We divided them into two groups: those admitted due to cardiological complaints and those admitted due to other reasons. Results: A total of 46 patients were affiliated with the group admitted for cardiological issues, while 58 were assigned to the group admitted for non-cardiological reasons. Upon further analysis of both groups regarding Lp(a) levels, it was observed that 14 out of the 46 patients (30.4%) admitted for cardiological reasons exhibited elevated lipoprotein levels ≥ 75 nmol/l. Thirteen (22.4%) out of the 58 patients in the group admitted for non-cardiological reasons demonstrated elevated Lp(a) levels. Except for HDL, no significant differences were observed between patients hospitalised due to cardiological and non-cardiological causes. Conclusions: The findings emphasise the importance of universal Lp(a) screening, particularly in individuals without signs of atherosclerosis, to identify those at risk.